Dative Alternation in Croatian - Zovko Dinković, Irena (Array, 2007)
Dative alternation is fairly rare in case-marking languages. However, Croatian exhibits this type of alternation with a small number of verbs. This paper analyzes the syntactic and semantic characteristics of Croatian dative verbs and their arguments, based on the data from the Croatian National Corpus, and attempts to determine the most appropriate theoretical framework for the description of dative alternation in Croatian. We prove that certain generalizations about the dative alternation are valid cross-linguistically, but we also show that this type of alternation exhibits many language specific features as well.